Evaluation of effect of ethanol extraction of Graptophyllum pictum on Zebrafish (Danio rerio) embryo model through toxicity assay assessment - Zainal Abidin, Azrina; Visepomaran, Subashini; Balan, Santhra Segaran; Bahari, Hasnah (ClinMed International Library, 2021)
Graptophyllum pictum is a medicinal plant that helps to cure different forms of disease due to the availability of beneficial phytochemicals such as flavonoids, steroids, alkaloids, saponins and glycosides. The purpose of this research was to evaluate the toxicity effect of G. pictum extract on zebrafish embryos (Danio rerio) at different concentrations. G. pictum was extracted using the ethanol method. A toxicity test was done by exposing the Danio rerio embryo to the G. pictum extraction at different concentrations (0.244-1000 μg/ml) for 24, 48, 72 and 96 hours. The survival rate, hatching rate, heartbeat rate, scoliosis rate and melanin pigmentation were observed. Data were analyzed using SPSS version 27. The value of LC50 was calculated. Result showed that the LC50, value of G. pictum is 7.662 μg/ml. No hatching was observed at higher concentrations (31.25-1000 μg/ml) while the hatch ability of Danio rerio embryos was observed at lower concentrations (0.244-1.953 μg/ml). Scoliosis of zebrafish larvae was not present at all concentrations. The heartbeat of the zebrafish larvae treated with G. pictum extract was within a normal range from 120-180 beats per minute at a lower concentration. Melanin pigmentation was detected at 48, 72 and 96 hours post-fertilization and is normally absent at 24 hours post-fertilization. As a conclusion, G. pictum extract stills exhibit a mild toxicity effect in higher concentrations when it was evaluated on zebrafish embryos.